The Religious Moderation in Kei Community, Maluku Indonesia: Upholds Local Wisdom, Religion, and Nationality as Vital Aspects - Ulum, Raudatul; Putro, Moh. Zaenal Abidin Eko (International Journal Ihya' 'Ulum al-Din, 2024)
Religiosity experiences moderation through encounters with sublime local cultures inherent in the Kei community in Maluku, Indonesia. This makes it worthy of research, especially regarding the integration of custom and religion. Kei culture was formed by the collective memory of their ancestors from Bali, Java, Banten, and other tribes in the archipelago. Conflicting gaps may arise due to paradoxes in cultural and religious life. This paper highlights the paradoxes and gaps between religious egalitarianism and traditional authority structures. It reports on interviews conducted with religious and traditional leaders, social and religious practitioners, and observations made during customary and religious activities in the Kei Islands. Data shows that religious followers' attitudes towards culture have a different quality. However, inclusion through traditional ceremonies is still maintained but the caste layer in custom has internal religious affairs. Likewise, in terms of national life, they have self-meaning as an open society. This paper concludes that accepting customary law can potentially create distortions and exacerbate the problem of changing diversity in life. If customs are managed well, they may stay within and outside the Kei community. Further research is necessary to explore how to rejuvenate the connection between traditional law and religion each time.